2021
DOI: 10.3390/jcm11010078
|View full text |Cite
|
Sign up to set email alerts
|

Association between Non-HDL-C/HDL-C Ratio and Carotid Intima–Media Thickness in Post-Menopausal Women

Abstract: Atherogenic lipoproteins (particularly, very low-density lipoproteins, VLDL) are associated with subclinical atherosclerosis. The present study aims at evaluating whether routinely analysed lipid parameters are associated with carotid intima–media thickness, a proxy for subclinical atherosclerosis. Lipid parameters from 220 post-menopausal women undergoing ultrasound investigation of the carotid arteries were analysed. Forty-five percent of women showed subclinical atherosclerosis on carotid ultrasound. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Furthermore, an analysis of 46 786 patients with type 2 diabetes showed that lower levels of non‐HDL‐C/HDL‐C are more effective risk markers for ASCVD compared to LDL‐C levels below 3 mmol/L 26 . In a primary prevention study conducted on 220 postmenopausal women, the non‐HDL‐C/HDL‐C ratio showed a stronger association with increased carotid intima‐media thickness in comparison to other lipid parameters 27 . Additionally, a study on 5822 Chinese individuals diagnosed with metabolic syndrome found a progressive increase in carotid intima‐media thickness across quartiles of the non‐HDL‐C/HDL‐C ratio, with no significant differences observed between the apoB/apoA1 ratio and non‐HDL‐C/HDL‐C ratio in predicting carotid atherosclerosis 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, an analysis of 46 786 patients with type 2 diabetes showed that lower levels of non‐HDL‐C/HDL‐C are more effective risk markers for ASCVD compared to LDL‐C levels below 3 mmol/L 26 . In a primary prevention study conducted on 220 postmenopausal women, the non‐HDL‐C/HDL‐C ratio showed a stronger association with increased carotid intima‐media thickness in comparison to other lipid parameters 27 . Additionally, a study on 5822 Chinese individuals diagnosed with metabolic syndrome found a progressive increase in carotid intima‐media thickness across quartiles of the non‐HDL‐C/HDL‐C ratio, with no significant differences observed between the apoB/apoA1 ratio and non‐HDL‐C/HDL‐C ratio in predicting carotid atherosclerosis 28 …”
Section: Discussionmentioning
confidence: 99%
“…26 In a primary prevention study conducted on 220 postmenopausal women, the non-HDL-C/HDL-C ratio showed a stronger association with increased carotid intimamedia thickness in comparison to other lipid parameters. 27 Additionally, a study on 5822 Chinese individuals diagnosed with metabolic syndrome found a progressive increase in carotid intima-media thickness across quartiles of the non-HDL-C/HDL-C ratio, with no significant differences observed between the apoB/apoA1 ratio and non-HDL-C/HDL-C ratio in predicting carotid atherosclerosis. 28 Lipoproteins containing apoB have a significant impact on the development and progression of atherosclerotic plaques by accumulating in the arterial intima, leading to atherogenic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Qin et al demonstrated that an increased non-HDL-c/HDL-c was signi cantly associated with elevated CIMT among Chinese individuals [37]. Among postmenopausal women, the non-HDL-c/HDL-c ratio was found to be signi cantly associated with CIMT [38,39]. Non-HDLc, which is calculated by TC minus HDL-c, provides a robust measure of the cholesterol content of all atherogenic lipoproteins as it also incorporates the potential risk conferred by high levels of atherogenic TG-rich remnants in addition to the risk due to LDL-c [40].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with type 2 diabetes who previously underwent coronary stent implantation, an elevated VLDL-C level >0.52 mmol/L was independently associated with in-stent restenosis (hazard ratio = 3.01) ( 21 ). Iannuzzi et al ( 22 ) used ultrasound to measure carotid intima–media thickness in postmenopausal women and showed that VLDL-C was the lipoprotein most strongly associated with subclinical atherosclerosis. In addition, evidence from clinical studies has consistently indicated a causal role for TG-rich lipoproteins such as VLDL in ASCVD.…”
Section: Independent Of Low-density Lipoprotein Very-low-density Lipo...mentioning
confidence: 99%